English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

C6H12O6(s) + O2(g) --> CO2(g) + H2O (g)

and

H2S(g) + SO2(g) --> H2O(g) + S(s)

and

C2H2(g) + --> CO2(g) + H2O(g)

2007-02-25 08:18:40 · 4 answers · asked by cb450t 3 in Science & Mathematics Chemistry

4 answers

so u need balancing
here it is my frnd

C6H12O6(s) + 6 O2(g) ---> 6 CO2(g) + 6 H2O(g)

2H2S(g) + SO2(g) ---> 2 H2O(g) + 3 S(s)

2 C2H2 (g) + 5 O2(g) ----> 4 CO2(g) + 2 H2O(g)


FOR MORE FEEL FREE AND MAIL UR QUESTIONS DIRECTLY TO ME WITHOUT LOSING PTS.
gaurav_genius88@yahoo.com

2007-02-25 08:35:19 · answer #1 · answered by   2 · 1 1

C6H12O6 + 6O2 --> 6CO2 (g) + 6H2O(g)

H2S(g) +1/2 SO2 (g) --> H2O(g) + 3/2S (s)

I think the last one is incomplete the left hand side should have an oxygen like this,

C2H2(g) +5/2O2(g) --> 2CO2(g) + H2O(g)

hope this will help u :)

2007-02-25 08:32:39 · answer #2 · answered by neng m 1 · 0 1

C6H12O6(s) + O2(g) --> CO2(g) + H2O (g)
C6H12O6 + 6O2 ---> 6CO2 + 6H2O

and

H2S(g) + SO2(g) --> H2O(g) + S(s)
2H2S + SO2 ---> 2H2O + 3S

and

C2H2(g) + --> CO2(g) + H2O(g)
Not a complete equation???

2007-02-25 08:26:45 · answer #3 · answered by Tyler C 2 · 0 1

C6H12O6+6O2--->6CO2+6H2O

2H2S+SO2--->2H2O+2S

2C2H2+5O2--->4CO2+2H2O

2007-02-25 09:48:19 · answer #4 · answered by science teacher 7 · 1 0

fedest.com, questions and answers